A Feasibility Study on MEDITECH LABORATORIES, INC. - Flores, Ma. Criselda; Gonzales, Cheryl Victoria; Javier, Nidalin (Diliman, Quezon City College of Engineering, 2004)
The need for excellent, inexpensive medical devices has been steadily increasing in recent years due to changing disease patterns, and the need to provide low-cost health care to all. Currently, the demand is satisfied by foreign firm that manufacture these device, at high costs. There is a great potential for MediTech Laboratories Inc., to enter the market and capture demand, through its research and development of PDA-based biomedical devices. A corresponding marketing plan was conceived which also includes the development of intelligent hospitals, a project that the company is to start by its fifth year. The total cost of promotion for the first year of operation is P34,158,714.00 The company will be outsourcing its production of finished goods. However, to ensure that the quality of its products, raw materials suppliers accredited by MediTech shall be the only sources of the components used by the EMS provider. Quality control personnel will likewise be sent to the EMS provider to ascertain if specifications are met. Funding for the project will be provided with a loan from the DOST-TAPI, Landbank of the Philippines and by the company?s issuance of company bonds. The profitability of the proposed establishment was established by the some positive figure, such as a 0.041 value for the Fixed Assets to Net Worth Ratio and a Net Turnover of 0.53 during the first year. The payback period of 0.2887 and manageable break-even figures are also indicative of financial feasibility. In summary, the project also has a positive Net Present Value P77,891,978 and an attractive Internal Rate of Return 22.88%. Meditech's mission and vision of helping each Filipino, regardless of wealth, in availing excellent health care services at an affordable price also makes it socially profitable. The company's role of developing the field of science and engineering in the society is also a portal for more meaningful innovations in the future. The above statements reiterate and verify the soundness of the project in terms of the presence and growth of a market, the logistics, machinery, and manpower needed, its profitability, and the benefits it will bring to society. Therefore this group confirms that the production of MediTech Laboratories Inc. in an industrial setting is feasible.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: MEDITECH LABORATORIES, INC; Medical electronics equipment industry; Participatory monitoring and evaluation (Project management)